BubR1 N Terminus Acts as a Soluble Inhibitor of Cyclin B Degradation by APC/C(Cdc20) in Interphase - Malureanu, Liviu A. (2009)
BubR1 is an essential mitotic checkpoint protein with multiple functional domains. It has been implicated in mitotic checkpoint control -as an active kinase at unattached kinetochores and as a cytosolic inhibitor of APC/C(Cdc20) activity- as well as in mitotic timing and stable chromosome-spindle attachment. Using BubR1-conditional knockout cells and BubR1 domain mutants, we demonstrate that the N-terminal Cdc20 binding domain of BubR1 is essential for all of these functions, whereas its C-terminal Cdc20-binding domain, Bub3-binding domain, and kinase domain are not. We find that the BubR1 N terminus binds to Cdc20 in a KEN box-dependent manner to inhibit APC/C activity in interphase, thereby allowing accumulation of cyclin B in G(2) phase prior to mitosis onset. Together, our results suggest that kinetochore-bound BubR1 is non-essential and that soluble BubR1 functions as a pseudosubstrate inhibitor of APC/C(Cdc20) during interphase to prevent unscheduled degradation of specific APC/C substrates.